Degradation of Acephate and Its Intermediate Methamidophos: Mechanisms and Biochemical Pathways - Lin, Ziqiu; Pang, Shimei; Zhang, Wenping; Mishra, Sandhya; Bhatt, Pankaj; Chen, Shaohua (Frontiers in Microbiology, 2020)
Acephate is an organophosphate pesticide that has been widely used to control insect pests in agricultural fields for decades. However, its use has been partially restricted in many countries due to its toxic intermediate product methamidophos. Long term exposure to acephate and methamidophos in non-target organisms results in severe poisonous effects, which has raised public concern and demand for the removal of these pollutants from the environment. In this paper, the toxicological effects of acephate and/or methamidophos on aquatic and land animals, including humans are reviewed, as these effects promote the necessity of removing acephate from the environment. Physicochemical degradation mechanisms of acephate and/or methamidophos are explored and explained, such as photo-Fenton, ultraviolet/titanium dioxide (UV/TiO2) photocatalysis, and ultrasonic ozonation. Compared with physicochemical methods, the microbial degradation of acephate and methamidophos is emerging as an eco-friendly method that can be used for large-scale treatment. In recent years, microorganisms capable of degrading methamidophos or acephate have been isolated, including Hyphomicrobium sp., Penicillium oxalicum, Luteibacter jiangsuensis, Pseudomonas aeruginosa, and Bacillus subtilis. Enzymes related to acephate and/or methamidophos biodegradation include phosphotriesterase, paraoxonase 1, and carboxylesterase. Furthermore, several genes encoding organophosphorus degrading enzymes have been identified, such as opd, mpd, and ophc2. However, few reviews have focused on the biochemical pathways and molecular mechanisms of acephate and methamidophos. In this review, the mechanisms and degradation pathways of acephate and methamidophos are summarized in order to provide a new way of thinking for the study of the degradation of acephate and methamidophos.